Enhancing capacitive performance of magnetite-reduced graphene oxide nanocomposites through magnetic fieldassisted ion migration - Nur Alya Syakirah, Abdul Jalil; Aboelazm, Eslam Atef Abdelaziz; Khe, Chengseong; Ali, Gomaa Abdelgawad Mohammed; Chong, Kwok Feng; Lai, Chin Wei; You, Kokyeow (Public Library of Science, 2024)
The transition towards renewable energy sources necessitates efficient energy storage systems to meet growing demands. Electrochemical capacitors, particularly electric double-layer capacitors (EDLCs), show promising performance due to their superior properties. However, the presence of resistance limits their performance. This study explores using an external magnetic field to mitigate ion transfer resistance and enhance capacitance in magnetite-reduced graphene oxide (M-rGO) nanocomposites. M-rGO nanocomposites with varying weight ratios of magnetite were synthesized and comprehensively characterized. Characterization highlighted the difference in certain parameters such as C/O ratio, the Id/Ig ratio, surface area and particle size that contribute towards alteration of M-rGO’s capacitive behaviour. Electrochemical studies demonstrated that applying a magnetic field increased specific capacitance by approximately 20% and reduced resistance by 33%. Notably, a maximum specific capacitance of 16.36 F/g (at a scan rate of 0.1 V/s) and 27.24 F/g (at a current density of 0.25 A/g) was achieved. These improvements were attributed to enhanced ion transportation and migration at the electrode/electrolyte interface, lowering overall resistance. However, it was also observed that the aforementioned parameters can also limit the M-rGO’s performance, resulting in saturated capacitive state despite a reduced resistance. The integration of magnetic fields enhances energy storage in nanocomposite systems, necessitating further investigation into underlying mechanisms and practical applications.